(untitled) (Altre Modernità, 2019)
The essay aims to explore the thought and work of Wilhelm von Humboldt (1767-1835) referring to the concept of utopia. Humboldt is known for his studies on Language, Philosophy, Aesthetics and Political Philosophy, but he is not considered a utopian thinker. Through the analysis of his mains works and his main ideas (language as organism, unity and diversity etc.) the essay tries to demonstrate that his work can be read as utopian. In his work utopia is not be considered as the project of a future better world, but as paradigm of knowledge (Denkform), intentional concept that pushes the man to educate himself and to work on the present.